Liberalisme versus Perfeksionisme? Sebuah Tinjauan Filsafat Politik tentang Relasi Antara Agama dan Negara - Otto Gusti Madung (Jurnal Ledalero, 2013)
Intolerance and violence in the name of religion often flare up in Indonesia. In this regard the state often fails, and indeed itself becomes part of the violation of the citizen’s right to religious freedom. One root of the problem is a confused understanding among law enforcers and among a part of the citizenship concerning the relationship between religion and the state, between private and public morality. This essay attempts to formulate a concept of the relationship between religion and the state from the perspective of two models from political philosophy, namely liberalism and perfectionism. Perfectionism offers a solution to the pathology of liberalism which tends to privatise the concept of the good life. In perfectionism the thematisation of the concept of the good life as in ideologies and religions has to be given a place in the public sphere. In Indonesia this role is taken by the national ideology of Pancasila. Pancasila requires that religious values be translated into public morality. Kata-kata Kunci: liberalisme, perfeksionisme, konsep hidup baik (agama), negara, Pancasila.